Internet of Things in Smart Grid: Applications, challenges, Conditions, Architecture- A Review - Prasad Bansode; Debraj Bhowmick; D. B. Pardeshi (International Journal of Electrical Machine Analysis and Design, 2024)
Future-generation intelligent optimisation in electrical system design is essential for managing electrical networks and distribution systems. It also requires interoperability variations in the implementation of physical or graphical models. The Internet of Things (IoT) plays a significant role in smart grids and distributed electricity systems. IoT enables the monitoring of the smart grid's electrical energy and facilitates the integration of real-time data into electrical grid architecture at various levels. Industrial automation is managed by IoT, making the Smart Grid and IoT reliable tools for analysing and tracking electrical statistics in the U.S. Currently, smart city technologies and infrastructure are leveraging IoT to upgrade SCADA systems and integrate remote controls based on microcontrollers. Smart grids offer enhanced grid reliability, efficient energy distribution, and real-time monitoring through IoT integration. This analysis examines the core components of IoT in smart grids, focusing on its applications, architecture, challenges, and operational conditions. Additionally, the report underscores the role of IoT in enabling a sustainable future and modernising energy infrastructure.
Keywords: IOT; Microcontroller; Smart grid; electrical energy; power grid; smart city; sustainable development